The Relationship between ABO Blood Type, Knowledge Level, Behavior, and Hypertension Status in Young Adults on Campus - Neni Oktiyani; Tini Elyn Herlina; Ricko Dharmadi Utama (Medical Laboratory Technology Journal, 2026)
Hypertension is a public health problem increasingly found among young adults, including college students. This study aims to analyze the relationship between ABO blood type, knowledge level, behavior, and hypertension status in young adults on campus. This study used an analytical survey method with a cross-sectional design. The study population consisted of all active students in the Medical Laboratory Technology Study Program at the Poltekkes Kemenkes Banjarmasin, with a sample size of 99 respondents selected using a total sampling technique. The researchers collected data through online questionnaires and blood pressure measurements. Data analysis used the Chi-Square test with a significance level of p<0.05. The results showed that the majority of respondents were female (80.8%), had normal blood pressure (67.7%), had good knowledge (69.7%), and had good behavior (58.6%). Statistical test results showed that gender (p=0.533), ABO blood type (p=0.916), and behavior (p=0.231) were not significantly associated with hypertension status. Conversely, knowledge level was significantly associated with hypertension status (p=0.044). This study concluded that knowledge level was associated with hypertension status, while ABO blood type and behavior showed no significant association. These findings highlight the importance of improving health literacy as part of hypertension prevention efforts in young adults.